Effective utilization of visible light (including ? > 600 nm) in phenol degradation with p-silicon nanowire/TiO2 core/shell heterojunction array cathode - Yu, H.; Li, Xin Yong; Quan, X.; Chen, S.; Zhang, Y. (American Chemical Society, 2009)
For the sake of utilizing the light-harvesting ability of Si in pollution control, the p-silicon nanowire (SiNW)/TiO2 core/shell heterojunction arrays have been synthesized. Based on the surface photovoltage (SPV) measurement, these p-SiNW/TiO2 heterojunction arrays display considerable SPV response to the light with wavelength ranging from 300 to 700 nm. Under the protection of TiO2 shell, the SiNW core could harvest visible light stably in aqueous solution. The resistivity of the starting Si wafer has a distinct influence on the cathodic behaviors of p-SiNW/TiO 2 arrays. The higher photocurrent is observed for the sample using the starting Si wafer with moderate resistivity, in contrast with those using high- or low-resistivity starting Si wafer. In the photoelectrocatalytic experiments of phenol degradation under visible light irradiation conditions, the kinetic constant using p-SiNW/TiO2 cathode (0.983 h-1) is 17.7 times larger than that (0.0523 h-1) of TiO2 film on p type Si wafer (p-Si/TiO2). This result demonstrates that p-SiNW/TiO2 cathode could utilize visible light todecomposephenol with a considerable efficiency. The mechanism of phenol degradation is considered that the photogenerated electrons from p-SiNW/TiO2 cathode could be scavenged by dissolved oxygen first, followed by generation of hydroxyl radicals species via a chain reaction, and finally phenol could be oxidized. By constructing this kind ofheterojunctions,manyothernarrow- bandgapsemiconductors might be utilized as photocatalysts in pollution control, consequently, the optimal sunlight harvesting would be achieved. © 2009 American Chemical Society.